Effect of maternal food habits in periconceptional life with the occurrence of birth defects - Shams, Nusrat; Laila, Alif; Parvin, Jobaida; Mohsin, Mohammad; Hosain, Ahmed (International Journal of Contemporary Pediatrics, 2023)
Background: Maternal periconceptional period can be defined as the critical window surrounding the period of conception. The periconceptional period consists of preconception, conception, implantation, placentation and embryo or organogenesis stages, and specific cellular events that occur during the distinct stages of embryogenesis. On the other hand, birth defects are structural changes present at birth that can affect almost any part of the body. They may affect how the body looks, works, or both. This study aimed to find maternal food habits in periconceptional life with the occurrence of birth defects. Methods: This case-control study was conducted in both the Pediatric Surgery and Medicine Department of Dhaka Shishu (children) Hospital, Dhaka, Bangladesh during the period from January 2012 to December 2013. In total 280 ‘0-364 days old infants’ were included as the study subjects and divided into two equal groups in number, cases having a structural birth defect and controls without any birth defect. A pretested questionnaire was introduced after getting informed written consent from the mothers. Data were analyzed by statistical package for the social sciences (SPSS) 16.0 version, by univariate, bivariate and multivariate analyses and were presented by tables and graphs. Results: In this study, most of the defects were distributed to the gastrointestinal system (18%), genito urinary system (16%), CVS (14%), NTD (13%), defect of the face (13%) and skull (11%). The isolated defect was in 80% of patients, multiple defects in 17% of patients and 3% syndromes were present. In this study, mothers ‘who took no meat/week’, ‘who took no fish/week’, ‘who took no egg/week’, ‘who took no milk/week’, experienced BD more and the difference was statistically significant (p<0.05) between the groups. However, mothers who took vegetables less than once/week experienced BD more frequently, but the difference between the groups was not statistically significant (p>0.05). Conclusions: In maternal food habits; less intake of meat, fish, milk and egg is significantly correlated with the occurrence of birth defects but there is not any significant correlation with vegetable intake.